A Skills beyond School Review of Germany - Fazekas, Mihály (OECD Publishing, 2013)
This report examines vocational education and training programs in Germany including how they are changing, how they are funded, how they are linked to academic and university programmes and how employers and unions can be engaged
Keywords: Education; Germany